Nitrogen-doped carbon nanotube-based bilayer thin film as transparent counter electrode for Dye-Sensitized Solar Cells (DSSCs) - Chan-Park, Mary B. (2013)
Carbon nanotubes (CNTs) have been widely considered as one of the promising candidates for replacing fluorine-doped tin oxide (FTO)/platinum (Pt) electrodes to reduce the fabrication cost of dye-sensitized solar cells (DSSCs). Here, we report that a bilayer transparent film containing N-doped CNTs (which are highly catalytic) and normal CNTs (which are highly conductive) as a counter electrode in DSSCs results in efficiencies up to 2.18 %, yet still maintains a good transparency with a transmittance of approximately 57 % at 550 nm.